Stiffness Modulus of Asphaltic Concrete Incorporating Coir Fibre and Subjected to Aging - Abdullahi Ali, Mohammed; Putra Jaya, Ramadhansyah; Etienne, Joseph Marie Delbrel; Choong, Wee Kang; Sien, Ti Kok; Haryati, Yaacob; Norhidayah, Abdul Hassan; Nor Hayati, Abdul Hamid; Noram Irwan, Ramli (EDP Sciences, 2018)
The aim of this paper is to investigate the performance response of a set of coir fibre modified asphalt samples subjected different ageing conditions and containing three different fibre contents. The laboratory experimental programs are indirect tensile test at 25°C and repeated load axial test at 40°C. The results showed that the fibres improved the mixture’s performance. The main findings obtained at 25°C for short and long-term ageing reveal that low fibre content at around 0.3% per aggregate weight display a stiffness modulus up to 14% higher than that of unmodified mixtures, hence showing that fibres may improve the bearing capacity and rut-resistance of asphalt mixtures. Conversely, as the amount of fibre increases to 0.5% and 0.7%, the stiffness decreases to the point of becoming unacceptably low, almost 80% lower than unmodified mixes stiffness. However the data also reveal that high fibre contents at 0.5% and above completely neutralize the impact of ageing on the mixture, indicating that fibre-modified mixtures would yield longer lives.